2009
DOI: 10.3340/jkns.2009.46.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Hemifacial Spasm Caused by a Huge Tentorial Meningioma

Abstract: A rare case of hemifacial spasm caused by an ipsilateral tentorial meningioma is described. Magnetic resonance imaging showed a huge tumor in the right cerebellar hemisphere, distant to the cerebello-pontine cistern. The facial-vestibulocochlear nerve complex was stretched by the shift of the brainstem and the right cerebello-pontine cistern was effaced. After removing the tumor, the hemifacial spasm resolved completely. We review our case with the pertinent literature regarding the etiological mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Some cases have reported that similar remote tentorial meningiomas caused trigeminal neuralgia or hemifacial spasm. 7 10) Ogasawara et al discussed that these phenomena may result from both compression and displacement of the brainstem and secondary neurovascular compression of the trigeminal nerve by the tumor. They termed these mechanisms as “remote effects.” 8) In addition to these mechanisms, Cancelli et al hypothesized that venous circulation disorders can contribute to these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases have reported that similar remote tentorial meningiomas caused trigeminal neuralgia or hemifacial spasm. 7 10) Ogasawara et al discussed that these phenomena may result from both compression and displacement of the brainstem and secondary neurovascular compression of the trigeminal nerve by the tumor. They termed these mechanisms as “remote effects.” 8) In addition to these mechanisms, Cancelli et al hypothesized that venous circulation disorders can contribute to these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Complete disappearance of HFS after total excision of the tumor without MVD indicates that HFS is caused by distant tumors that do not involve the ipsilateral CPA. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[2] Vascular compression at the nerve exit zone is the most common cause of hemifacial spasm as evident by excellent results of microvascular decompression in many patients [1,3] and can now be demonstrated preoperatively due to availability of advanced magnetic resonance (MR) techniques like MR angiography and constructive interference in steady state (CISS) sequence. [4,5] In approximately 0.3% to 0.6% cases, hemifacial spasm is due to the mass lesion in the cerebellopontine (CP) angle cistern, [6] like epidermoid, meningioma, arachnoid cyst,andschwannoma. [3] Epidermoid is the third most common CP angle mass after schwannonaand meningioma.…”
mentioning
confidence: 99%
“…In many cases, there is associated vascular loop causing compression of facial nerve, while in some cases, the compressive effect may be due to tumor itself. [3,6] It has also been suggested that epidermoid may also cause direct irritation of facial nerve due its contents namely keratin and cholesterol. [3] In conclusion, hemifacial spasm can rarely be caused by CP angle masses like epidermoid.…”
mentioning
confidence: 99%
See 1 more Smart Citation